COMPUTER MEDIATED COMMUNICATION (CMC) DALAM PERSPEKTIF KOMUNIKASI LINTAS BUDAYA (Tinjauan Pada Soompi Discussion Forum Empress Ki TaNyang Shipper) - Fatma Dian Pratiwi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This essay attempts to see the practice of computer mediated communication of soompi discussion forum TaNyang shipper trough intercultural communication perspective. By using computer mediated social learning theory that emphasize closeness between the partisipant of the CMC despite of their phisical absence like in the personal communication does. The partisipants discusses and analyses everything about this TaNyang couple from the drama Empress Ki as well as about the Korean culture such as language, fashion, music, dancing and food. Because they presented in the drama so well that like it or not partisipants have to be familiar with it.This is the excellence of the Korean goverment that has policy spreading korean culture trough drama. So that the partisipant of this forum who come from all over the country around the world and have their own culture have been united by communicating one culture, Korean.